Relevance and irrelevance theories, factors and challenges - Nasu, Hisashi, 1949-; Strassheim, Jan (Age of access? Grundfragen der Informationsgesellschaft ;, 2018)
The buzzwords ""Information Society"" and ""Age of Access"" suggest that information is now universally accessible without any form of hindrance. Indeed, the German constitution calls for all citizens to have open access to information. Yet in reality, there are multifarious hurdles to information access - whether physical, economic, intellectual, linguistic, political, or technical. Thus, while new methods and practices for making information accessible arise on a daily basis, we are nevertheless confronted by limitations to information access in various domains. This new book series assemble.